Drilling of bone: numerical and experimental investigations - Fernandes, M.G.A. (2018)
Implant failures and post-operative problems may occur after implant placement as a result of the inappropriate conditions during drilling. The analysis of different materials and drilling parameters is crucial to reduce the bone damage and contribute to the success of this medical interventions. In this research, the effect of drilling parameters on the generated stresses and temperatures in the bone during the process was investigated.